Campylobacter fetus foodborne illness outbreak in the elderly - Grouteau, Gaspard; Mignonat, Cédric; Marchou, Bruno; Martin-Blondel, Guillaume; Glass, Olivier; Roubaud-Baudron, Claire; Lansalot-Matras, Pauline; Alik, Simon; Balardy, Laurent; De Nadaï, Thomas; Bénéjat, Lucie; Jehanne, Quentin; et al. (Frontiers in Microbiology, 2023)
In June 2021, a cluster of 7 cases of Campylobacter fetus infections occurred in a rehabilitation center, and caused significant morbidity in elderly patients including 5 with bacteremia and 2 with osteoarticular medical device infections. The genetic identity identified by whole genome sequencing of the different Campylobacter fetus strains confirms a common source. This foodborne illness outbreak may have resulted from consumption of unpasteurized dairy products, a cow's raw milk cheese resulting from a farm to fork strategy.